Stratiform barite deposits between Sarkikaraagac (Isparta) and Huyuk (Konya) in Sultandag region, Turkey - Ayhan, A (Urban & Fischer Verlag, 2001)
The most important and mineable barite deposits located between Huyuk and Sarkikaraagac in the southwestern part of the Sultandag region of western Taurus in Turkey occur essentially in a zone with an extension of 12 km in the Yellice and Kuyucak formations of Silurian-Devonian age. Barites were formed as a stratiform type, and are hosted by carbonates and pelitic rocks. Although these rocks have undergone weak metamorphism to the greenschist facies, sufficient indications of primary depositional fabrics were preserved in the barite layers and lenses. They show sedimentary and diagenetic structures such as the banded, layered nature of barite, rhythmicity, cross-bedding, geopetal fabrics, and diagenetic recrystallization. Sulfur isotope data from barite samples indicate that the sulfate ions were supplied from coeval seawater. According to the present data, the barites were deposited in a basin with an irregular paleotopography influenced by the synsedimentary faults. The probably source of barium was brines derived from the Seydisehir Formation.
Keywords: Pb